COLLABORATION PROCESS AS ACCOUNTABILITY STRATEGY IN POVERTY REDUCTION POLICY IN MERAUKE DISTRICT - Wister Hitapea; Alwi Alwi; Gita Susanti; Muhammad Hidayat Djabbari (Enrichment : Journal of Management, 2022)
One of the policies that are the focus of this research is the accountability of poverty alleviation policies. Poverty is a complex 'problem' throughout the world, especially for developing countries including Indonesia. It is said to be complex, because poverty affects various aspects of life both socially, economically and politically. For this reason, collaborative efforts are needed in solving poverty problems that are effective and efficient. This study aims to analyze the collaboration process as an accountability strategy in poverty alleviation policies in Merauke Regency. This study uses a descriptive qualitative approach. Data was collected through interviews, observation and documentation studies. Data processing and analysis techniques are carried out by data reduction, data display, and conclusion drawing/verification. Determination of informants using purvosive sampling technique. The results of the research show that the collaboration process in the accountability of poverty policy implementation in Merauke Regency which is carried out by the Merauke Regency regional government has not been maximally implemented due to several aspects of cross-sectoral collaboration such as: a) Forging agreement; b) Building leadership; c) Building legitimacy; d) Building trusts; e) Managing conflicts; and f) Planning, has not been implemented properly in order to reduce poverty in Merauke Regency. The results of the research show that the collaboration process in the accountability of poverty policy implementation in Merauke Regency which is carried out by the Merauke Regency regional government has not been maximally implemented due to several aspects of cross-sectoral collaboration such as: a) Forging agreement; b) Building leadership; c) Building legitimacy; d) Building trusts; e) Managing conflicts; and f) Planning, has not been implemented properly in order to reduce poverty in Merauke Regency. The results of the research show that the collaboration process in the accountability of poverty policy implementation in Merauke Regency which is carried out by the Merauke Regency regional government has not been maximally implemented due to several aspects of cross-sectoral collaboration such as: a) Forging agreement; b) Building leadership; c) Building legitimacy; d) Building trusts; e) Managing conflicts; and f) Planning, has not been implemented properly in order to reduce poverty in Merauke Regency.